Understanding the FinTech continuance intention of Indonesian users: the moderating effect of gender - Nurlaily, Ferina; Aini, Edlyn Khurotul; Asmoro, Priandhita Sukowidyanti (Business: Theory and Practice, 2021)
This research attempt to analyze risk and benefit factors as well as their influence on sustainability intention of FinTech. We elucidate the Planned Behavior Theory by including the perceived benefits and perceived risk variables to investigate its effect on intention to continue using FinTech. We also examined whether or not men and women are affected differently by the benefits and risk they perceive when using FinTech. Data were collected through online surveys, then being analyzed using GSCA. The results reveal perceived benefits are affected significantly by the convenience aspect and deliver a significant effect on FinTech continuance intention. The risk perceived by FinTech users is affected the most by legal risk. This study proves that gender is able to moderate the perceived risk influence on the intention to continue using FinTech, especially in the female user group.